Rhino-orbito-cerebral with cutaneous mucormycosis - Ezzy, Mustafa K.; Kulkarni, Pushkaraj A.; Patekar, Shivali K.; Shah, Kshitij D.; Bradoo, Renuka A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
"Mucormycosis" term is used for a group of fungal diseases caused by the order mucorales. It typically presents as sino-nasal-orbital involvement and rarely involves skin. Management of such cases is quite challenging. Reported here is a case of a young girl, who presented with right eye swelling and reduced vision and got detected with type 1 diabetes mellitus on admission with rare occurrence of cutaneous lesions while on treatment. Direct nasal endoscopy with biopsy was undertaken. KOH and histopathology report was suggestive of mucormycosis, for which the patient was administered intravenous amphotericin B and surgical debridement was carried out. With the accurate application of a multidisciplinary approach with timely investigations, imaging studies, antifungals and debridement, successful outcome in mucormycosis is well within our reach.